2007
DOI: 10.1029/2006ja011773
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variations in the equatorial vertical drift in the topside ionosphere

Abstract: [1] The vertical ion drift is important for understanding and modeling the electrodynamics at low latitudes. Measurements from the ion drift meter on the Defense Meteorological Satellite Program (DMSP) F15 are used to examine longitudinal variations in the vertical ion drift at the dip equator in the topside ionosphere. Local time was restricted to 0930 and the data were organized by month for 2001 and 2002. Two features were found contributing to the longitudinal variations in the electrodynamics. Meridional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 23 publications
12
127
1
Order By: Relevance
“…As denoted by the thin lines vertical between Figures 4a and 4b, the peak locations of upward E × B drift are close to those of nmf2, at least for the southern EIA crest, while the longitude of the wave 1 peak does not match between the upward E × B drift and the nmf2 at the northern EIA crest; this is discussed later. Compared with observations of vertical drift, the significant existence of the wave 4 structure agrees with existing observations [Hartman and Heelis, 2007;Kil et al, 2007Kil et al, , 2008Ren et al, 2009]. However, the amplitude of wave 4 is considerably lower in our simulation (about 4%) than in the observations (e.g., about 10% is shown in Figure 2 of Ren et al [2009] for a similar local time and season).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As denoted by the thin lines vertical between Figures 4a and 4b, the peak locations of upward E × B drift are close to those of nmf2, at least for the southern EIA crest, while the longitude of the wave 1 peak does not match between the upward E × B drift and the nmf2 at the northern EIA crest; this is discussed later. Compared with observations of vertical drift, the significant existence of the wave 4 structure agrees with existing observations [Hartman and Heelis, 2007;Kil et al, 2007Kil et al, , 2008Ren et al, 2009]. However, the amplitude of wave 4 is considerably lower in our simulation (about 4%) than in the observations (e.g., about 10% is shown in Figure 2 of Ren et al [2009] for a similar local time and season).…”
Section: Resultssupporting
confidence: 90%
“…The nonmigrating tides, with their climatology, have been observed directly in the lower thermosphere [e.g., Oberheide et al, 2006;Forbes et al, 2008], which confirmed the dominant existence of the DE3 tide during many months. As evidence of modulation in the dynamo, a four-peak structure has been observed in E × B drift [Hartman and Heelis, 2007;Kil et al, 2007Kil et al, , 2008Ren et al, 2009] and in the equatorial electrojet (EEJ) [England et al, 2006b;Luhr et al, 2008] and has been shown in electrodynamic simulations [Jin et al, 2008;Ren et al, 2010]. Furthermore, the four-peak structure of the EIA has been reproduced by a simulation using the ThermosphereIonosphere-Mesosphere-Electrodynamics General Circulation Model (TIME-GCM), in which the nonmigrating tidal forcing derived from the Global-Scale Wave Model was incorporated at its lower boundary [Hagan et al, 2007].…”
Section: Introductionmentioning
confidence: 92%
“…Oh (oh@spweather.com) 2007; Scherliess et al, 2008). The observations of similar periodic structures in the daytime equatorial electrojet (England et al, 2006a;Mouël et al, 2006) and equatorial vertical ion velocity on the topside (Hartman and Heelis, 2007;Kil et al, 2007) supported the association of the longitudinal density structure with the daytime vertical drift of equatorial plasma. The diurnal non-migrating eastward-propagating tide with zonal wave number-3 (DE3 tide) was suggested as the driver of the longitudinal variation of the vertical E×B drift (England et al, 2006a, b;Immel et al, 2006) and Hagan et al (2007) and showed the capability to produce the observed wave-4 density structure by the effect of the DE3 tide.…”
Section: Introductionmentioning
confidence: 85%
“…Such measurements provide comprehensive coverage with respect to local time, seasonal, and solar activity dependences at one geographic location. In situ satellite-based observations from spacecraft such as Atmosphere Explorer, Dynamics Explorer 2, San Marco, DMSP, ROCSAT-1, and C/NOFS (e.g., Maynard et al, 1988Maynard et al, , 1995Coley and Heelis, 1989;Coley et al, 1994;Hartman and Heelis, 2007;Huang et al, 2010;Fejer et al, 2013) have been used to examine ionospheric drifts (or equivalently electric fields) over spatially more extensive regions, with the limitation of mixing local time, latitude, and longitude. The electric fields measured, in turn, are the result of a complicated electrodynamic interaction between the E and F regions that varies greatly from day to night.…”
Section: Introductionmentioning
confidence: 99%